2004
DOI: 10.1515/znc-2004-5-617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Activity of the Acetone Extract of the Lichen Ramalina farinacea and its (+)-Usnic Acid, Norstictic Acid, and Protocetraric Acid Constituents

Abstract: The acetone extract of the lichen Ramalina farinacea and its (+)-usnic acid constituent showed antimicrobial activity against Bacillus subtilis, Listeria monocytogenes, Proteus vulgaris, Staphylococcus aureus, Streptococcus faecalis, Yersinia enterocolitica, Candida albicans, and Candida glabrata. Norstictic acid was active against Aeromonas hydrophila as well as the above microorganisms except Yersinia enterocolitica. Protocetraric acid showed activity only against the tested yeasts Candida albicans and Candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 1 publication
4
76
1
4
Order By: Relevance
“…All the tested extracts showed antibacterial properties, bioactivity being in the order EtOH > n-hexane > CHCl 3 > water extract (Esimone & Adikwu, 1999). Also, Tay et al (2004) evaluated the acetone extract of the lichen Ramalina farinacea in Turkey and showed antimicrobial activity against B. subtilis, Listeria monocytogenes, P. vulgaris, S. aureus, Streptococcus faecalis, Yersinia enterocolitica, Candida albicans, and C. glabrata. They demonstrated that (þ)-usnic acid, a constituent of Ramalina farinacea, is the major antimicrobial agent in this lichen (Tay et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the tested extracts showed antibacterial properties, bioactivity being in the order EtOH > n-hexane > CHCl 3 > water extract (Esimone & Adikwu, 1999). Also, Tay et al (2004) evaluated the acetone extract of the lichen Ramalina farinacea in Turkey and showed antimicrobial activity against B. subtilis, Listeria monocytogenes, P. vulgaris, S. aureus, Streptococcus faecalis, Yersinia enterocolitica, Candida albicans, and C. glabrata. They demonstrated that (þ)-usnic acid, a constituent of Ramalina farinacea, is the major antimicrobial agent in this lichen (Tay et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Tay et al (2004) evaluated the acetone extract of the lichen Ramalina farinacea in Turkey and showed antimicrobial activity against B. subtilis, Listeria monocytogenes, P. vulgaris, S. aureus, Streptococcus faecalis, Yersinia enterocolitica, Candida albicans, and C. glabrata. They demonstrated that (þ)-usnic acid, a constituent of Ramalina farinacea, is the major antimicrobial agent in this lichen (Tay et al, 2004). When the inhibition zones obtained from R. farinaceae in this study were compared with Ramalina species in our study, maximum antibacterial efficiency among all Ramalina species in Turkey was exhibited by Ramalina farinaceae.…”
Section: Discussionmentioning
confidence: 99%
“…Several lichen extracts and their compounds have been used in traditional medicine in Europe, Asia and Northern America (Richardson, 1988;Tilford, 1997). Scientific investigation of the biological activity of lichen extracts and their constituents includes in vitro and in vivo studies on antimicrobial, immunostimulating, antioxidative, antiulcerogenic, analgesic/antipyretic and antiinflammatory properties of lichens (Kumar and Müller, 1999;Huneck, 2001;Ingolfsdottir, 2002;Türk et al, 2003;Tay et al, 2004;Yilmaz et al, 2004;Halici et al, 2005;Behera et al, 2006;Choudhary et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Antiparasitic effects have been described for several species of lichen. Hayward and Rosentreter (1994) found that G. sabrinus selected lichens containing the secondary compounds norstictic acid, fumarprotocetraric acid, vulpinic acid and atranorin, all of which have been attributed with varying degrees of antiparasitic or antimicrobial effects (Giez et al 1994;Tay et al 2004;Yilmaz et al 2004). These various studies support the possibility that the use of T. occidentalis, as well as several lichen species, by G. sabrinus and T. hudsonicus may be a behavioural adaptation for ectoparasite control in the nest environment.…”
Section: Discussionmentioning
confidence: 90%